Filaggrin loss‐of‐function mutations, atopic dermatitis and risk of actinic keratosis: results from two cross‐sectional studies. (6th March 2017) - Andersen, Y.M.F.; Egeberg, A.; Balslev, E.; Jørgensen, C.L.T.; Szecsi, P.B.; Stender, S.; Kaae, J.; Linneberg, A.; Gislason, G.; Skov, L.; Elias, P.M.; Thyssen, J.P.
Abstract: Background: Common loss‐of‐function mutations in filaggrin gene ( FLG ) represent a strong genetic risk factor for atopic dermatitis (AD). Homozygous mutation carriers typically display ichthyosis vulgaris (IV) and many have concomitant AD. Previously, homozygous, but not heterozygous, filaggrin gene mutations have been associated with squamous cell carcinomas. Objective: The first objective was to examine the association between FLG mutations and actinic keratosis (AK). The second objective was to investigate the occurrence of AK in patients with IV and AD, respectively. Methods: FLG mutation status in patients with AK was compared with controls from the general population. Furthermore, based on nationwide data from Danish registers, we compared the risk of AK in patients with IV, AD and psoriasis, respectively. Results: The prevalence of homozygous FLG mutations was significantly higher in the AK group ( n = 4, 0.8%) in comparison with the control group ( n = 18, 0.2%), whereas the prevalence of heterozygous FLG mutations was lower. In hospital registry data, patients with AD exhibited an increased risk of AK than did psoriasis controls (adjusted OR 1.46; [95% CI 1.12–1.90]), whereas no difference in risk was observed between patients with IV and AD. Conclusions: This study indicates an increased susceptibility to AK in individuals with homozygous, but not heterozygous, FLG mutations and in patients with AD compared to psoriasis. Whether a reduction or absence of epidermal filaggrin could contribute to the susceptibility to AK in patients with IV and AD is unknown and additional research is needed to further explore this relationship.